EDUCATION 4.0: TECHNOLOGICAL REVOLUTION OR DISGUISED THREAT? - Costa Júnior, João Fernando; Giese, Waldir; Schimidt, Marcelo Queiroz; Huber, Norberto; da Costa, Jonas Bezerra; de Abreu, Simone Feliciano; de Barros, Maria José; de Mendonça, Mariana Santos; da Silva, Inailma Elisa; de Oliveira, Alline Paula Santos; dos Santos, Ivete Bispo; Ferreira, Anselmo Accioly Francisco; et al. (Seven Editora, 2025)
This article offers a critical analysis of Education 4.0, addressing its concepts, foundations, and challenges from an integrative perspective. Initially, it contextualizes Education 4.0 within the context of Industry 4.0 and digital culture, highlighting the ambivalence between pedagogical innovation and risks to the human dimension of education. The methodology adopted, an integrative literature review, ensured the necessary breadth to understand multiple facets of the phenomenon. The text details the pedagogical potential of emerging technologies, such as artificial intelligence and augmented reality, and the importance of active methodologies and personalized learning for the development of 21st-century skills. It also discusses the essential digital skills for students and teachers, emphasizing the importance of continuing education that articulates technical, critical, and ethical aspects. It explores inequalities in access to technological infrastructure, demonstrating that "digital inclusion" needs to go beyond the mere provision of devices to be defined as social justice. The article also addresses risks associated with technological dependence, information overload, and the commodification of education, which threaten the mental health of those involved and the autonomy of the educational project. Finally, it proposes that Education 4.0 will be a pedagogical revolution with robust public policies, an integrated curriculum, ethical data governance, and qualified teacher training, while it will become a threat when dominated by market and technical interests. The article concludes by emphasizing the need for a careful balance between innovation and humanization, and suggests future research agendas to deepen the understanding of the sociocultural impacts of this educational transformation. DOI: https://doi.org/10.56238/sevened2025.038-074